Efficiency of General Insurance in Malaysia Using Stochastic Frontier Analysis - Mohamad Arif Awang Nawi; Wan Muhamad Amir W Ahmad; Nor Azlida Aleng (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2011)
General insurance comprises insurance of property against fire and burglary, floods, storms,earthquakes and so on. The purpose of the current study is to measure the relative efficiency of generalinsurance in Malaysia by using SFA for the year 2007 until 2009, consist of 26 general insurancecompanies by using the software FRONTIER to obtain the maximum likelihood (ML) and to get therelative efficiency. The finding showed that Oriental Capital Assurance Bhd (OCA) is at rank 1 for thethree years. The 0.03975 value for the variance gamma ( γ ) parameter in this study is far from one,suggesting that all of the residual variations are not due to the inefficiency effects, but to randomshocks. It can therefore, be concluded that the technical inefficiency effects associated with theproduction of the total profits by the input of the general insurence are very low.